1959
DOI: 10.1126/science.129.3340.42
|View full text |Cite
|
Sign up to set email alerts
|

Critical Period for Effects of Infantile Experience on Maturation of Stress Response

Abstract: Manipulated infant rats respond to cold with depletion of adrenal ascorbic acid (AAA) significantly earlier than nonmanipulated infants. The study discussed in this report examined the critical period for infantile manipulation on the depletion of AAA. It was found that infant rats manipulated immediately following birth exhibited significant AAA depletion, whereas infants manipulated later did not exhibit depletion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
62
0

Year Published

1959
1959
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(66 citation statements)
references
References 1 publication
4
62
0
Order By: Relevance
“…For example, manipulations during the first week of life have different effects on maternal behavior and limbic-hypothalamicpituitary-adrenal (LHPA) axis development from manipulations in the second week of life Ader, 1969, 1974;Levine and Lewis, 1959;Meaney and Aitken, 1985;Reisbick et al, 1975). Likewise, we would expect to see differences in drug-taking behavior in animals who were manipulated during week 1 compared to week 2 of life.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…For example, manipulations during the first week of life have different effects on maternal behavior and limbic-hypothalamicpituitary-adrenal (LHPA) axis development from manipulations in the second week of life Ader, 1969, 1974;Levine and Lewis, 1959;Meaney and Aitken, 1985;Reisbick et al, 1975). Likewise, we would expect to see differences in drug-taking behavior in animals who were manipulated during week 1 compared to week 2 of life.…”
Section: Introductionmentioning
confidence: 91%
“…The exact timing of a stressor, the regimen of exposure, and the resulting maternal behavior elicited by early life manipulations seem to play a critical role in determining long-term outcomes (Denenberg and Bell, 1960;Denenberg and Zarrow, 1971;Levine and Lewis, 1959;Nunez et al, 1996;Ogawa et al, 1994;Russell, 1971). For example, manipulations during the first week of life have different effects on maternal behavior and limbic-hypothalamicpituitary-adrenal (LHPA) axis development from manipulations in the second week of life Ader, 1969, 1974;Levine and Lewis, 1959;Meaney and Aitken, 1985;Reisbick et al, 1975).…”
Section: Introductionmentioning
confidence: 99%
“…What mechanisms [8,9,[12][13][14]19] mediated the increased basal and cold-induced plasma CORT subsequent to maternal deprivation? An increase of basal plasma CORT and PVN-CRH-mRNA abundance in adult rats subjected to maternal separation in infancy has been reported [16].…”
Section: Introductionmentioning
confidence: 99%
“…Using this paradigm, maternal deprivation alone resulted in an increased basal and acute stress-induced plasma CORT level compared to maternal and sibling deprivation. This was not associated with excess weight loss in either group (see above), excluding thermal-loss as the cause of the enhanced stress response.What mechanisms [8,9,[12][13][14]19] mediated the increased basal and cold-induced plasma CORT subsequent to maternal deprivation? An increase of basal plasma CORT and PVN-CRH-mRNA abundance in adult rats subjected to maternal separation in infancy has been reported [16].…”
mentioning
confidence: 99%
“…Levine and Lewis (1959) have demonstrated that rats handled at 2 to 5 days (Gr. I) and to 13 days after birth (Gr.…”
Section: Locomotive Activity and Estrus Cycles In Rats Subjected To Imentioning
confidence: 99%